Shaping Comparative Linguistics: The Achievement of Franz Bopp: Moldando a Linguística comparada: a conquista de Franz Bopp - Swiggers, Pierre (Revista do GEL, 2025)
Franz Bopp (1791-1867) is commonly regarded as one of the founding fathers of Indo-European comparative grammar. Bopp’s primary interest was in the origin of grammatical forms, a goal he pursued, from 1816 on, through the analytical comparison of formative processes of inflectional word classes in Sanskrit, Greek, Latin, German, and Persian in a first stage (other Indo-European languages were progressively included in his scholarly spectrum). The larger part of Bopp’s work was in the field of Sanskrit, but his interest in the unitary mother language (Stammsprache) led him to write the first comparative grammar of Indo-European (published in three volumes over the years 1833-1852); this comprehensive work (of which a second edition appeared in 1857-1861, and a third in 1868-1871) was preceded and followed by studies in which Bopp applied an analytical procedure to the segmentation, the classification and the explanation of grammatical forms. The present contribution examines the assumptions or hypotheses underlying Bopp’s work, and the resulting claims (regarding the structure of Indo-European roots, the constitution of grammatical forms, and the content-side of grammatical morphemes), with an eye to Bopp’s intellectual and institutional position as well as to his appraisal by contemporaries and by subsequent generations of scholars.